Between theology and religion : Ibn Taymiyyah’s methodological approach and its contemporary relevance - Abdullah, Ismail (International Islamic University Malaysia, 2011)
Religious beliefs and theological scrutiny of those beliefs exist side by side with each other from the time immemorial. Religious beliefs seek to continuously characterise and regenerate values, feelings, imaginations and actual daily activities of a person whosoever. Theology stands to scrutinize such religious beliefs, thoughts and values to see whether these beliefs and values are sustainable in human life based on reasoning. Although there is hardly any distinctive single definition for theology, it is said to be the rational inquiry into religious matters such as the nature of God and the truth of the sacred scriptures or, in a broader sense, it is a system of thought which attempts to present what we can know and understand about God in an organised and understandable manner. However, throughout the human history, questions related to the rapport between religion and theology particularly whether that relationship is harmonious or contradictory and what are the proper rational theological means to understand and interpret the nature of God as well as God’s Words, have long been the main concern of theologians, philosophers as well as religious scholars. Ibn Taymiyyah (1263-1328) was one of the prominent Muslim theologians who endeavoured to comprehend the nature of this relationship and produced numerous volumes on this subject. Ibn Taymiyyah maintains that religion and theology are not contradictory to each other; they are both rather complementary to each other. He believes that the religious teachings can be further clarified and validated through the application of theological approach. He also raises the question as to the nature of the theological methodology. He invites the philosophers to deliberate over the issue whether the matters concerning the religion are purely rational. It seems that Ibn Taymiyyah’s concern and suggestions are of universal nature, thus making them still relevant to the 21st century world. This paper seeks to explain his methodological approach to religion and theology with a view to substantiating its contemporary relevance. Analytical and comparative methods will be applied in this paper.